Impact of Coronavirus Disease 2019 Pandemic on the Incidence and Management of Out‐of‐Hospital Cardiac Arrest in Patients Presenting With Acute Myocardial Infarction in England - Rashid (Hons), Muhammad (J Am Heart Assoc, 2020)
BACKGROUND: Studies have reported significant reduction in acute myocardial infarction–related hospitalizations during the coronavirus disease 2019 (COVID‐19) pandemic. However, whether these trends are associated with increased incidence of out‐of‐hospital cardiac arrest (OHCA) in this population is unknown. METHODS AND RESULTS: Acute myocardial infarction hospitalizations with OHCA during the COVID‐19 period (February 1–May 14, 2020) from the Myocardial Ischaemia National Audit Project and British Cardiovascular Intervention Society data sets were analyzed. Temporal trends were assessed using Poisson models with equivalent pre–COVID‐19 period (February 1–May 14, 2019) as reference. Acute myocardial infarction hospitalizations during COVID‐19 period were reduced by >50% (n=20 310 versus n=9325). OHCA was more prevalent during the COVID‐19 period compared with the pre–COVID‐19 period (5.6% versus 3.6%), with a 56% increase in the incidence of OHCA (incidence rate ratio, 1.56; 95% CI, 1.39–1.74). Patients experiencing OHCA during COVID‐19 period were likely to be older, likely to be women, likely to be of Asian ethnicity, and more likely to present with ST‐segment–elevation myocardial infarction. The overall rates of invasive coronary angiography (58.4% versus 71.6%; P<0.001) were significantly lower among the OHCA group during COVID‐19 period with increased time to reperfusion (mean, 2.1 versus 1.1 hours; P=0.05) in those with ST‐segment–elevation myocardial infarction. The adjusted in‐hospital mortality probability increased from 27.7% in February 2020 to 35.8% in May 2020 in the COVID‐19 group (P<.001). CONCLUSIONS: In this national cohort of hospitalized patients with acute myocardial infarction, we observed a significant increase in incidence of OHCA during COVID‐19 period paralleled with reduced access to guideline‐recommended care and increased in‐hospital mortality.